Intervention strategies to reduce maternal mortality in Peru. - Távara Orozco, Luis (2015)
More than a decade that Peru made a commitment to reach a level of health for Peruvians in 2000 that allows us a socially and economically productive level. Within this context, albeit some countries on the continent have already achieved many of the objectives proposed by the Region of the Americas, we are far from achieving and according to the evolution of the facts and the missing years to finish the century is reasonable to accept that lack a greater commitment and effort in excess of that has been making to date to deal with this noble challenge.